Effect of bariatric surgery on circulating and urinary mitochondrial DNA copy numbers in obesity with or without diabetes. Issue 1 (5th October 2020) - Seo, Mihae; Kim, Hyoungnae; Noh, Hyunjin; Jeon, Jin Seok; Byun, Dong Won; Kim, Sang Hyun; Kim, Hye Jeong; Suh, Kyoil; Park, Hyeong Kyu; Kwon, Soon Hyo
Abstract : Introduction: Recent studies have suggested that extracellular circulating and urinary mitochondrial DNA (mtDNA) are associated with mitochondrial dysfunction in obesity and type 2 diabetes mellitus (T2DM). However, the changes to cell-free serum and urinary mtDNA after bariatric surgery in patients with obesity with T2DM have not been investigated to date. Research design and methods: We prospectively recruited patients with obesity (n=18), and with obesity and T2DM (n=14) who underwent bariatric surgery, along with healthy volunteers (HV) as a control group (n=22). Serum and urinary mitochondrial nicotinamide adenine dinucleotide dehydrogenase subunit-1 (mtND-1) and cytochrome-c oxidase 3 (mtCOX-3) copy numbers were measured using quantitative PCR (qPCR). The mtDNA copy numbers of patients with obesity (with and without T2DM) were followed up 6 months after surgery. Results: The copy numbers of urinary mtND-1 and mtCOX-3 in patients with obesity, with or without T2DM, were higher than those in the HVs. Moreover, urinary mtCOX-3 copy number increased in patients with obesity with T2DM compared with patients with obesity without T2DM (p=0.018). Meanwhile, serum mtCOX-3 copy numbers in HV were higher in both obesity patient groups (p=0.040). Bariatric surgery reduced urinary mtND-1 and mtCOX-3 copy numbers, as well as serum mtCOX-3 copy numbers only in patients with obesity with T2DM. Conclusion: These results suggest that T2DM induces greater kidney mitochondrial dysfunction in patients with obesity, which can be effectively restored with bariatric surgery.